PEMBERDAYAAN KARANG TARUNA DALAM PERINTISAN WIRAUSAHA SABLON DESA PASANGGRAHAN KECAMATAN UJUNG BERUNG BANDUNG - Reza Kurniawan; Endang Susilawati; Vini Rizqi; Albert Kurniawan Purnomo (Indonesian Collaboration Journal of Community Services, 2022)
The purpose of this Community Service activity is to develop youth groups economically and socially and to improve skills in screen printing entrepreneurship for youth in Karang Taruna, Pasanggrahan Village, Ujung Berung District, Bandung City. The methods in this activity are: 1) Material Preparation, 2) Material Counseling, 3) Group Distribution, 4) Screen Printing Training, 5) Screen Printing Practice Implementation. The expected output targets in this Community Service program are expected to increase the interest of the youth of Karang Taruna, Psanggrahan Village, Ujung Berung Subdistrict, Bandung City to increase income with independent businesses through screen printing entrepreneurs. enthusiastic and received a positive response and participants became more motivated to innovate and provide solutions for participants to start new businesses, reduce unemployment and also to improve the family economy